2019
DOI: 10.1515/aut-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

The Use of New Technologies for the Development of Protective Clothing: Comparative Analysis of Body Dimensions of Static and Dynamic Postures and its Application

Abstract: In this research, the use of new technologies for the development of special protective overall for sport aircraft pilots was studied, with a focus on a comparative analysis of the static and dynamic body postures’ dimensions, intended for the development of the overall’s pattern design. For this purpose, digitalization of five male persons was carried out with the 3D human body scanner Vitus Smart by using 3D printed markers, precisely positioned on defined body locations, intended for exact measurement of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Thus, it still needs to be investigated especially for specific sports in order to achieve fit in sportswear. The body measurement changes were evaluated by Bogovic et al (2018) in dynamic sitting postures simulating inside the aircraft [26] and by Wu and Kuzmichev (2018) in six dynamic postures simulating diving [27]. However, unlike the present research, these studies do not include detailed information about dynamic positions such as body angles.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, it still needs to be investigated especially for specific sports in order to achieve fit in sportswear. The body measurement changes were evaluated by Bogovic et al (2018) in dynamic sitting postures simulating inside the aircraft [26] and by Wu and Kuzmichev (2018) in six dynamic postures simulating diving [27]. However, unlike the present research, these studies do not include detailed information about dynamic positions such as body angles.…”
Section: Introductionmentioning
confidence: 82%
“…It was concluded that successful performance in the sport of archery could be influenced by the archer's physical attributes. In order to develop the patterns of the protective overall for sport aircraft pilots, Bogovic et al (2018) focused on comparative analysis between the static and dynamic body postures [26]. They took measurements of five male subjects in static posture and three different postures namely standing posture with arms forward, standing posture in a forward bend, and sitting posture with arms stretched towards knees.…”
Section: Introductionmentioning
confidence: 99%
“…Pri tem je zelo pomembna faza jemanje mer, kot tudi virtualna simulacija oblačila s krojnimi deli, prilagojenimi sedečemu položaju. Ključne besede: funkcionalna oblačila, invalidi, 3-D skeniranje, virtualna simulacija oblačil Tekstilec, 2019, 62 (1), [23][24][25][26][27][28][29][30][31][32][33] Computational Design of Functional Clothing for Disabled People paraplegia, multiple sclerosis, muscular dystrophy and other disorders of the locomotor system) are most aff ected [1]. Th e most frequently used disability classifi cation, drawn up by the World Health Organisation (ICIDH), classifi es disabilities as: behaviour disabilities, communication disabilities, personal care disabilities, locomotor disabilities, particular skill disabilities and situational disabilities.…”
Section: Izvlečekmentioning
confidence: 99%
“…By changing the design and resizing the projected seam, a model that facilitates a bend of more than 130º at the knees and trunk is created, with no change in trouser fi tting and the functionality of a garment for wheelchair users. Th e use of tailored pieces and the simulation generated positive Figure 8: Developing trouser patterns for people in the sitting position [65] Figure 7: 3D human body animations in diff erent positions [60] Tekstilec, 2019, 62(1), [23][24][25][26][27][28][29][30][31][32][33] Computational Design of Functional Clothing for Disabled People results, which is evident in prototyping. However, this method of design cannot be applied to all wheelchair users, as garment design depends on a person's individual needs and body morphology [61−63].…”
Section: Virtual Garment Design For People With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation